CHALLENGES RELATED TO UNMANNED AERIAL VEHICLES - Tomaszycki Marek; Krawczyk Jacek (2021)
Abstract The Regulation of the European Parliament and of the Council (EC) No. 2018/1139 (known as NBR - New Basic Regulation) on common rules in the field of civil aviation was introduced in order to regulate the issue of UAVs - Unmanned Aerial Vehicles, in all weight categories. It represents a new regulatory approach, which is of major importance in the field of European aviation legislation. Until the new regulation came into force, UAVs with a maximum take-off weight (MTOM) below 150 kg were subject to the regulations of authorities of individual EU Member States. The NBR introduced by implementing acts in the field of UAV forces the national aviation authorities of states to change the regulations currently in force. The most important issues that need to be standardised include the requirement to enter UAVs with the MTOW equal to or lower than 25 kg in the aircraft register, granting the BVLOS (Beyond Visual Line of Sight) fight approval and the UAVO (Unmanned Aerial Vehicle Operator) certification process. In the author's opinion, what may be difficult and dangerous for safety in the airspace is the transitional period. During that time, manufacturers, airspace users and ATS (Air Traffic Service) will have to perform their tasks keeping in mind that it is a period when the new legal regulations currently prepared for entry into force will affect the entire sector related to unmanned aviation, which will also have an impact on manned aviation. Purpose: The purpose of the article is to discuss the basic challenges posed by the currently developed technology of unmanned aerial vehicles. Method: The scientific methods used in the paper include analysis, criticism of the literature on the subject and logical construction. Results: The article shows the differences between the existing regulations and those proposed by the European Commission and EASA (European Union Aviation Safety Agency). In addition, it presents the process of granting the approval to perform air operations by manned aircraft.